Thermo-mechanical properties of digitally-printed elastomeric polyurethane: Experimental characterisation and constitutive modelling using a nonlinear temperature-strain coupled scaling strategy. (1st April 2023) - Yang, Jie; Liao, Zisheng; Hossain, Mokarram; Huang, Guanyu; Zhou, Xin; Liu, Fan; Alzaidi, Ahmed S.M.; Yao, Xiaohu
Abstract: The Additive manufacturing (AM) technology has emerged as a novel paradigm that uses the method of gradual accumulation of materials to manufacture solid parts, which is a "bottom-up" approach compared to the traditional cutting technology. Among available techniques, Digital Light Synthesis (DLS) further facilitates the opportunity for continuous building instead of the layer-by-layer or the dot-by-dot printing approach, thus curtailing the time of production and encouraging the development of many new materials. In this contribution, temperature-dependent mechanical properties of a DLS-based 3D-printed elastomeric polyurethane (EPU) are investigated by utilising experimental characterisation and constitutive modelling. Specifically, uniaxial tensile and stress relaxation tests under temperature fields ranging from −20 °C to 60 °C are performed, which reveal deformation-nonlinearity and temperature-sensitivity of the elastomer. This temperature range covers the glass transition of the polymer. Experimental results show that the temperature-dependence is also correlated with strain levels. Motivated by the experimental results, a phenomenologically-inspired thermodynamically-consistent constitutive model is formulated to characterise the finite deformation behaviours of EPU. In this case, for the first time, a single temperature-strain coupled function can capture the thermo-mechanical behaviour across the glass transition. Satisfactory accuracy of the prediction can be seen using the proposed constitutive model. This study contributes to the fundamental understanding of the mechanical properties of DLS-based digitally-printed EPU under a wide temperature field. The comprehensive thermo-mechanical experimental characterisation and subsequent constitutive modelling will facilitate the designing of other 3D-printed soft materials. Highlights: Uniaxial tensile tests are performed on 3D–printed PU across the glass transition. Temperature dependence is found to correlate with strain levels. A thermodynamically–consistent constitutive model is proposed. Thermo–mechanical behaviours across the glass transition are captured by the model. Satisfactory accuracy of the model in predictions is demonstrated.